2019
DOI: 10.4018/978-1-5225-8482-7.ch001
|View full text |Cite
|
Sign up to set email alerts
|

Modernization and Accountability in the Social Economy

Abstract: This chapter aims to systematically review the literature on modernization and accountability practice in the social economy. The collection of bibliography to support this systematic review was made in several scientific databases, only considering documents written in English. The criteria for researching the documents used in the development of this chapter are explained in the section that presents the methodology. It is possible to verify that only two articles published in the 20th century, 1997 and 1999… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…As we saw in the previous point, several authors have been developing frameworks for the social economy sector, but there is still no framework to be used more generally. Furthermore, the studies present the frameworks, but do not present their application to the reality, except for very specific applications or regarding a specific dimension, as can be concluded from our review of the literature and reinforced with the systematic review carried out by Santos et al [31]. This fact may be associated with the difficulty related to obtaining data, largely due to the low use of ICT in this sector.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…As we saw in the previous point, several authors have been developing frameworks for the social economy sector, but there is still no framework to be used more generally. Furthermore, the studies present the frameworks, but do not present their application to the reality, except for very specific applications or regarding a specific dimension, as can be concluded from our review of the literature and reinforced with the systematic review carried out by Santos et al [31]. This fact may be associated with the difficulty related to obtaining data, largely due to the low use of ICT in this sector.…”
Section: Methodsmentioning
confidence: 85%
“…In order to improve the sustainable development of social economy organizations on the one hand, and to increase stakeholder confidence on the other, the need to combine modernization and accountability was documented by Santos, Ferreira, Marques, Azevedo and Inácio [31]. They also highlighted the importance of designing quality internal control mechanisms, as a guarantee of good accountability practices, alignment and integration of all stakeholders, raising performance and trust levels, thus resulting not only in individual growth but also in community development.…”
Section: Accountability In Social Economymentioning
confidence: 99%
“…A recent systematic literature review (Santos et al, 2019) concluded that studies on the social economy are still very few, despite the tendency of growing. It stated that modernization has an impact on the economic and social aspects of entities of the social economy and also showed that the practice of transparency and accountability are elements of recognized merit for the good performance of these entities.…”
Section: Literature Review Transparency and Accountabilitymentioning
confidence: 99%
“…Some frameworks to promote transparency and accountability in its various dimensions are still very scarce. There are some studies on accountability, but not all on the social economy sector (Santos et al, 2019). For example, there is a study that developed a practical framework which can be used to explore how accountability within social enterprise organizations is constructed and discharged.…”
Section: Literature Review Transparency and Accountabilitymentioning
confidence: 99%
See 1 more Smart Citation